NICPS 17 propiedad, planta y equipo: impacto en el patrimonio del gobierno central. - Pizarro Barzallo, Roxana Mariuxi (Universidad Técnica de Machala, 2022)
Several countries are implementing the International Accounting Standards for the Public Sector (IPSAS), under the guarantee that this promotes the quality of accounting information and improves transparency and accountability by the public administration. The present research work "IPSAS 17 PROPERTY, PLANT AND EQUIPMENT: IMPACT ON THE EQUITY OF THE CENTRAL GOVERNMENT", aims to analyze the impact of the Equity of the Central Government from the implementation of IPSAS 17 Property, Plant and Equipment of the Sector Non-Financial Public. As a methodology, the descriptive technique was used through bibliographic reviews, accounting regulations, books, scientific articles, among other texts considered important for the foundation of this work. Finally, a practical case was proposed where it is evident that at the time of recognizing a long-lived good or an asset, it also symbolizes an increase in equity, in such a way that recognizing and applying correctly would mean that the information is reasonable in the financial statements.
Varios países se encuentran implementando las Normas Internacionales de Contabilidad para el sector Público (NICSP), bajo la garantía de que con ello se promueve la calidad de información contable y se mejora la transparencia y rendición de cuentas por parte de la administración pública. El presente trabajo de investigación “NICSP 17 PROPIEDAD, PLANTA Y EQUIPO: IMPACTO EN EL PATRIMONIO DEL GOBIERNO CENTRAL”, tiene como objetivo analizar el impacto del Patrimonio del Gobierno Central a partir de la implementación de la NICSP 17 Propiedad, Planta y Equipo del Sector Público no Financiero. Como metodología se utilizó la técnica descriptiva mediante revisiones bibliográficas, normativa contable, libros, artículos científicos, entre otros textos considerados importantes para la fundamentación de este trabajo. Finalmente, se planteó un caso práctico en donde se evidencia que al momento de reconocer un bien de larga duración o un activo, este también simboliza un incremento del patrimonio, de tal manera que reconocer y aplicar correctamente, significa que la información es razonable en los estados financieros.
Keywords: NICSP; PROPIEDAD PLANTA Y EQUIPO; CONTABILIDAD GUBERNAMENTAL; SECTOR PÚBLICO